Soybean cropping systems on sandy soil of the Caiuá Sandstone formation in Northwestern Paraná, Brasil - Bordin, Ivan; Silva, Nilson dos Santos; Silva, Tiago Roque Benetoli da; Santos, Josiane Bürkner; Gil, Luciano Grillo; Canalli, Lutécia Beatriz dos Santos; Hojo, Ronaldo Hissayuki; Llanillo, Rafael Fuentes (Semina: Ciências Agrárias, 2020)
Extensive cattle ranching had been the most common farming practice in northwestern Paraná State (Brazil), where soils originate from the Caiuá Sandstone. But this reality is changing with the growing cultivation of grain crops, especially soybeans. This study aimed to evaluate different soybean cropping systems in terms of yield components, plant dry matter, and soil chemical properties. The soil is classified as a dystrophic sandy Red Argisol, which derived from the Caiuá Sandstone, in northwestern Paraná State (Brazil). The experiment was carried out in the city of Umuarama (PR), Brazil, under a no-till system for three years. Treatments consisted of the following crop rotation systems: T1: congo grass/soybeans, congo grass/soybeans, congo grass/soybeans; T2: black oats + rye/soybeans, black oats + radish/grain sorghum, black oats + rye/soybeans; T3: triticale/corn, grain sorghum/soybeans, triticale/ soybeans; T4: crambe/grain sorghum, canola/corn, safflower/soybeans; T5: lupine/corn + congo grass, beans/corn, buckwheat/black oats/congo grass. The experiment was arranged in a randomized block design, with four replications and 300-m2 plots. The data were subjected to analysis of variance, and means were compared by the Tukey's test at 5% significance. The highest grain yield was obtained when soybeans were sown after white oats harvesting. Plant dry matter increased in the system with lupine/corn + congo grass, beans/corn, buckwheat/white oats/soybeans. However, none of the systems had an effect on soil chemical properties during the three crop years.